Recurrence of hepatocellular carcinoma following liver transplantation. (2nd January 2021) - Hoffman, Daniel; Mehta, Neil
ABSTRACT: Introduction: Hepatocellular carcinoma (HCC) is an increasingly common disease with liver transplant (LT) the best long-term therapy for early stage disease. We will review the data for assessing risk and managing recurrence for patients undergoing LT for HCC. Areas Covered: In this review, we will provide an overview of methods of patient risk stratification in the post-transplant period, the data around surveillance for HCC recurrence, and the evidence for and against post-LT adjuvant treatment strategies. Finally, we will provide data regarding treatment options for patients with HCC recurrence after LT. Using an extensive search of original papers and society guidelines, this paper provides a comprehensive review of the data for assessing risk and managing recurrence for patients undergoing LT for HCC. Expert Opinion: The development of multiple post-transplant prognostic scoring systems have allowed for improved assessment of recurrence risk and stratification of patients. However, the ability to translate this information into surveillance and therapeutic strategies that improve patient outcomes still have to be fully demonstrated. Post-LT immunosuppression strategies have been implemented in order to attempt to reduce this risk. Evidence-based strategies for managing recurrent HCC are evolving. We expect that with further understanding of individual patient characteristics will allow for optimal therapeutic selection.